Anti-influenza A virus activity and structure–activity relationship of a series of nitrobenzoxadiazole derivatives. (1st January 2021) - Fiorentino, Francesco; De Angelis, Marta; Menna, Martina; Rovere, Annarita; Caccuri, Anna Maria; D'Acunzo, Francesca; Palamara, Anna Teresa; Nencioni, Lucia; Rotili, Dante; Mai, Antonello
Abstract: Influenza viruses represent a major threat to human health and are responsible for seasonal epidemics, along with pandemics. Currently, few therapeutic options are available, with most drugs being at risk of the insurgence of resistant strains. Hence, novel approaches targeting less explored pathways are urgently needed. In this work, we assayed a library of nitrobenzoxadiazole derivatives against the influenza virus A/Puerto Rico/8/34 H1N1 (PR8) strain. We identified three promising 4-thioether substituted nitrobenzoxadiazoles (12, 17, and 25 ) that were able to inhibit viral replication at low micromolar concentrations in two different infected cell lines using a haemagglutination assay. We further assessed these molecules using an In-Cell Western assay, which confirmed their potency in the low micromolar range. Among the three molecules, 12 and 25 displayed the most favourable profile of activity and selectivity and were selected as hit compounds for future optimisation studies. Graphical abstract: UF0001